Sensitivity of computable general equilibrium models to macroeconomic closure rules: Evidence from the IFPRI standard mode - Laborde Debucquet, David; Traoré, Fousseini (International Food Policy Research Institute, 2017)
In this paper, we study the sensitivity of computable general equilibrium (CGE) models to the choice of macroeconomic closure rule using the case of the standard IFPRI model for Nigeria and Tanzania. Two sets of simulations are performed: a 50 percent decrease in import taxes and a 10 percent increase in agricultural productivity. For each simulated scenario, we study around 10 closure rules related to the government, the rest of the world, the investment-savings equilibrium, and the factors market. We find that the model’s solutions are sensitive to the choice of the macroeconomic closure rule.